The Paradigm Shift In Food Preservation: Thermal And Non-Thermal Processes - Nabilah, Uray Ulfah; Oktaviani, Sulha Rahmi (FoodTech: Jurnal Teknologi Pangan, 2024)
The changes in consumer prevalence in the selection of thermal and non-thermal processes are closely related to paradigm shifts. The study of paradigm changes in process technology will provided information in the development of food processing technology. This review aimed to analyse the paradigm shift of thermal and non-thermal processes in ontology, axiology, and epistimology, and to study the driving factors of the paradigm shift based on literature studies. The existence of thermal process technology was started from food safety issues that led to various modern food processing innovations. The recorded inventions included the processing of food products in hermetic containers at high temperatures, product packaging, variations of sterilization and pasteurisation methods, autoclave equipment, prediction of thermal process adequacy, and process hurdles. A problem of thermal process applications in food industry is the over-process that leads to degradation of product quality. The awareness of the importance of health and the environment has been shifting public perception from thermal processes to non-thermal alternative processes. Non-thermal processes have been proven to be a food preservation technology because it can inactivate microbes and minimise product quality losses. The mechanism of microbial inactivation depends on the type of technology used. The types of non-thermal process technologies include pulsed UV-light, ultrasound, irradiation, cold plasma, pulsed electric fields, and high hydrostatic pressure. The presence of thermal and non-thermal processes has provided a wide variety of new innovations, but for optimal optimisation, more studies are required in the future.